Studi Risiko Penggunaan Kayu Bakar Terhadap Kejadian Bayi Berat Lahir Rendah - Widaryana, I Dewa Made; Setiani, Onny; Adi, M. Sakundarno (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2003)
ABSRACT Background : Low birth weight incidence in Central Java is still high (1.2 %) compare to birth life. Faktor that may cause low birth weight intrinsic factors (i.e. mothers nutrition, anemia, etc.), and extrinsic factors i.e. physical factor, chemist, and social economic. One of chemical factor was carbon monoxide exposure from wood smoke. Fire wood consumption in Central Java is still high ( Rp.3.093, - per capita) compare to gasoline consumption (Rp.1.093/per capita) and Liquid Petroleum Gas (Rp.43, - per capita). The main objective of this research is to measure the risk of the using of fire wood to low birth weight incidence. Methods :This research a case control study, that used 84 low birth weight infant for case, compare to 84 non low birth weight infant for control and infant mothers as respondents. Results :The research show that the using of fire wood has OR=1.493 95%CI= 0.801-2.783, period time wood fuel before pregnant (in year) result OR=1.118;95%CI = 0.581-2.151, exposure duration before pregnant (hours/day) has OR=1.402 ;95% CI= 0.761-2.582, exposure duration in pregnant (in trimester) has OR=1.538;95%CI= 0.837 – 2.826, exposure duration in pregnant (hours/day) result OR=1.471 ;95% CI=0.799-2.708. Conclusion : There is no significant influence of the using of fire wood to low birth weight in Semarang District. Supposed for another researchers, to research in stage II (ambient) and stage III (biomarker), because this research is only in stage I (sources) and stage IV (impact). Key Words : Fire woodl, Low Birth Weight, Semarang District, 2002